New Learning Scenarios with Chatbots – Conversational Learning with Jix: from Digital Tutors to Serious Interactive Fiction Games - Kowald, Cäcilie; Bruns, Beate (International Journal of Advanced Corporate Learning (iJAC), 2019)
Conversational user interfaces, aka chatbots, offer new ways of interaction that can be used not only for task-led applications, but also for learning itself. Conversational learning offers a variety of new and extensive options to support individuals through the learning process and to push the boundaries of classroom based learning. This document shows three application scenarios that have been realized with time4you’s conversational learning software Jix. After having read this text, you will have a better idea of what conversational learning is, how it can be used in learning and development, and what is critical for its success.